Marking Landscape - Árdís Sigmundsdóttir 1963- (2019)
My lifelong interest in all kinds of outdoor activities led to this project. It is well known that being in natural environment has positive effects on our mental and physical health. In terms of design, the Icelandic landscape offers infinite possibilities to experience design and explore our sensory experience in a natural environment where well-being and the nourishing of body and soul are paramount. In this project, the walking path to the volcano Mount Helgafell in Hafnarfjörður is marked with audio material and can deepen people’s experience of the landscape. Visitors are invited to join locals who share their knowledge on audio recordings that can be accessed through a mobile phone. Marking Landscape is concerned with making information about the environment around Mount Helgafell accessible for the public. The aim was to have the information very clear and understandable and use theories about environmental aesthetic and perception, as a background.